A Neutral and Aromatic Boron‐Rich Inorganic Benzene. (26th February 2020) - Ota, Kei; Kinjo, Rei
Abstract: A neutral 1, 4‐diaza‐2, 3, 5, 6‐tetraborinine derivative (3 ) featuring a 6π ring system has been synthesized and structurally characterized. The prospective aromatic nature of 3 was assessed by single‐crystal X‐ray analysis, NMR, and UV/Vis absorption spectroscopy as well as computational studies. Furthermore, preliminary reactivity investigations showed that 3 does not only react with diphenyl acetylene but also readily captures CO2 in a [4+2] cycloaddition under ambient conditions. Abstract : Wer braucht schon Kohlenstoff? Ein rein anorganisches Benzolderivat mit einem sechsgliedrigen B4 N2 ‐Ring wurde synthetisiert. Strukturmerkmale und theoretische Studien deuten auf einen ausgeprägten aromatischen Charakter und die deutliche Delokalisierung von sechs π‐Elektronen im B4 N2 ‐Ring hin. In [4+2]‐Cycloadditionen mit ungesättigten Molekülen erweist sich der Ring als sehr reaktiv.